Gadolinium-based MRI characterization of leptomeningeal inflammation in multiple sclerosis. (7th July 2015) - Absinta, Martina; Vuolo, Luisa; Rao, Anuradha; Nair, Govind; Sati, Pascal; Cortese, Irene C.M.; Ohayon, Joan; Fenton, Kaylan; Reyes-Mantilla, María I.; Maric, Dragan; Calabresi, Peter A.; Butman, John A.; et al.
Abstract : Objective: To determine the frequency and nature of leptomeningeal contrast enhancement in multiple sclerosis (MS) via in vivo 3-tesla postcontrast T2-weighted, fluid-attenuated inversion recovery (FLAIR) MRI and 7-tesla postmortem MRI–pathology correlation. Methods: Brain MRI, using the postcontrast T2-weighted, FLAIR technique, was prospectively collected in 299 MS cases and 37 age-matched neurologically healthy controls. Expert raters evaluated focal gadolinium enhancement in the leptomeningeal compartment. Two progressive MS cases came to autopsy after in vivo MRI characterization. Pathologic and immunohistochemical examination assessed the association of enhancement with leptomeningeal inflammation and adjacent cortical demyelination. Results: Focal contrast enhancement was detected in the leptomeningeal compartment in 74 of 299 MS cases (25%) vs 1 of 37 neurologically healthy controls (2.7%; p = 0.001). Enhancement was nearly twice as frequent ( p = 0.009) in progressive MS (39/118 cases, 33%) as in relapsing-remitting MS (35/181, 19%). Enhancing foci generally remained stable throughout the evaluation period (up to 5.5 years). Pathology showed perivascular lymphocytic and mononuclear infiltration in the enhancing areas in association with flanking subpial cortical demyelination. Conclusion: Leptomeningeal contrast enhancement occurs frequently in MS and is a noninvasive, in vivo marker of inflammation and associated subpial demyelination. It might therefore enable testing of new treatments aimed at eliminating this inflammation and potentially arresting progressive MS.